2015
DOI: 10.1542/peds.2014-2806
|View full text |Cite
|
Sign up to set email alerts
|

Case Report of GNAS Epigenetic Defect Revealed by a Congenital Hypothyroidism

Abstract: Pseudohypoparathyroidism (PHP) is a group of disorders characterized by end-organ resistance to the parathyroid hormone (PTH). PHP type 1A includes multihormone resistance syndrome, Albright's hereditary osteodystrophy, and obesity and is caused by mutations in GNAS exon 1 through 13. PHP type 1B (PHP1B), caused by epigenetic changes in the GNAS locus, was initially described as an isolated resistance to PTH. Epigenetic changes in GNAS have also been reported in patients who display mild Albright's hereditary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…Subsequent analyses have demonstrated that some patients with PHP1B display additional features that overlap with PHP1A. As in PHP1A, PTH resistance might not be present at birth and develops only over time [44][45][46][47][48][49][50] . TSH resistance and patterns of excessive intrauterine growth or weight gain at birth or during early infancy and childhood have been described 44,51,52 .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequent analyses have demonstrated that some patients with PHP1B display additional features that overlap with PHP1A. As in PHP1A, PTH resistance might not be present at birth and develops only over time [44][45][46][47][48][49][50] . TSH resistance and patterns of excessive intrauterine growth or weight gain at birth or during early infancy and childhood have been described 44,51,52 .…”
Section: Methodsmentioning
confidence: 99%
“…Brachydactyly develops over time and might not be evident in early life, except in patients with acrodysostosis 6,35,86 . The frequency and severity of brachydactyly vary among the different disorders: 70-80% in PHP1A 51 , 15-33% in PHP1B 46,51,70,[87][88][89][90][91][92][93] and all patients with acrodysostosis 5,6,14,15,20,[62][63][64][94][95][96] (Table 1). However, brachydactyly is not specific to PHP and related disorders and can be found in patients with, for example, tricho-rhino-phalangeal syndrome, brachydactyly mental retardation syndrome or Turner syndrome (Table 2).…”
Section: The Definition Of Pth Resistance Is As Followsmentioning
confidence: 99%
See 3 more Smart Citations